2019
DOI: 10.1111/jeb.13575
|View full text |Cite
|
Sign up to set email alerts
|

Ecological divergence and speciation in common bottlenose dolphins in the western South Atlantic

Abstract: Coastal and offshore ecotypes of common bottlenose dolphins have been recognized in the western South Atlantic, and it is possible that trophic niche divergence associated with social interactions is leading them to genetic and phenotypic differentiation. The significant morphological differentiation observed between these ecotypes suggests they represent two different subspecies. However, there is still a need to investigate whether there is congruence between morphological and genetic data to rule out the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 96 publications
1
41
0
Order By: Relevance
“…Although different tissues were analysed when comparing studies, the observed δ 13 C values showed divergence possibly induced by the habitat use of the species in different regions of the Brazilian coast. Therefore, our results reinforce previous studies, which have described the existence of two stocks of bottlenose dolphins showing differences in their distribution, that are individuals in estuarine-shallow coastal waters south of 28°S and individuals in coastal-oceanic waters north of 28°S (see Costa et al ., 2019). However, there are no available investigations regarding isotopic values from latitudes lower than Rio de Janeiro state along the Brazilian coast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different tissues were analysed when comparing studies, the observed δ 13 C values showed divergence possibly induced by the habitat use of the species in different regions of the Brazilian coast. Therefore, our results reinforce previous studies, which have described the existence of two stocks of bottlenose dolphins showing differences in their distribution, that are individuals in estuarine-shallow coastal waters south of 28°S and individuals in coastal-oceanic waters north of 28°S (see Costa et al ., 2019). However, there are no available investigations regarding isotopic values from latitudes lower than Rio de Janeiro state along the Brazilian coast.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, morphological and genetic evidence has indicated that two distinct forms inhabit the South-western Atlantic Ocean (SAO): one in the south and the other in the north of 28°S. According to the authors, these forms appear to show differences in cranial morphology and a variation in their distribution (see Ott et al ., 2016; Fruet et al ., 2017; Costa et al ., 2019). The southern form is usually sighted in salt lagoons and estuaries of the southern coast of Brazil, Uruguay and Argentina (see Simões-Lopes & Fabian, 1999; Fruet et al ., 2011; Giacomo & Ott, 2016; Wickert et al ., 2016; Genoves et al ., 2018), and has been proposed as a new species for the genus, T. gephyreus (see Wickert et al ., 2016; Genoves et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic and phenotypic characterization of populations associated with different habitats (Costa et al, 2021) (Choo et al, 2021; van der Ven et al, 2020), similar to the role of wind for dispersing seeds of terrestrial plants. Thus, the comparison of patterns of dispersal predicted from biophysical models with those inferred from genetic data allows us to understand how currents influence speciation in the sea (Sjöqvist et al, 2015).…”
Section: Identifying the Main Reproductive Barriers Between Marine mentioning
confidence: 98%
“…Here, we tested for parallel evolution driven by ecological niche specialization in a highly social marine mammal, the common bottlenose dolphin, which has a worldwide temperate and tropical distribution. Two ecotypes of common bottlenose dolphins (coastal and pelagic, also called offshore) have recurrently formed in multiple regions of the world (25)(26)(27)(28)(29). Coastal populations were suggested to have been founded from pelagic source populations (25)(26)(27)30).…”
Section: Mainmentioning
confidence: 99%
“…Bottlenose dolphins (Tursiops sp.) also exhibit complex behaviors, such as habitat specialisation or social learning of foraging techniques, that strongly influence their patterns of genetic variability (28,31,38), and we hypothesize that these also facilitate their ability to adapt to novel conditions.…”
Section: Mechanisms Of Parallel Evolution To Coastal Habitatmentioning
confidence: 99%